2015
DOI: 10.1007/s10865-015-9620-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tobacco smoking abstinence among tuberculosis patients in South Africa

Abstract: This study examines predictors of smoking cessation in tuberculosis patients with high HIV co-infection rates in a South African primary care setting. Current smokers were randomly allocated to brief motivational interviewing (n=205) or receipt of a brief message (n=204).Multi-level logistic regression was performed to identify predictors of sustained 3-and 6-month abstinence and 7-day point prevalence abstinence (PPA) at 1 month, with the facility as a random effect. The intervention was ineffective among smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Similarly, Pradeepkumar et al 42 and Nichter et al 41 found that most relapses occurred after completion of treatment. Short duration of pharmacotherapy might influence the number of patients who quit smoking, according to the randomized controlled study of Sharma et al 18 . Possessing a disease-specific cessation message and focusing on all forms of tobacco use may decrease the probability of tobacco-dependence relapse 29 , 40 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Pradeepkumar et al 42 and Nichter et al 41 found that most relapses occurred after completion of treatment. Short duration of pharmacotherapy might influence the number of patients who quit smoking, according to the randomized controlled study of Sharma et al 18 . Possessing a disease-specific cessation message and focusing on all forms of tobacco use may decrease the probability of tobacco-dependence relapse 29 , 40 .…”
Section: Resultsmentioning
confidence: 99%
“…All studies but one (in French) were published in English. Eight of the included studies were RCS [13][14][15][16][17][18][19][20] , 28 articles reported on non-randomized studies . Characteristics of the studies and their main findings are presented in Tables 1 and 2.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…51 Both qualitative and quantitative studies of TB patients who have and those who have not successfully quit smoking would further elucidate what was most helpful about specific interventions, how interventions impact patients beyond just smoking cessation, such as improving overall quality of life, and other factors that contribute to smoking cessation, such as self-efficacy. 52,53 Nichter et al included qualitative interviews of patients who continued smoking after the 6-month TB treatment period and intervention. 14 These interviews suggested that the smokers did not see low-level smoking as harmful and that they resumed smoking to demonstrate that they were healthy enough to smoke.…”
Section: Research Implicationsmentioning
confidence: 99%